2021
DOI: 10.3390/ijerph18073585
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Studies on Bisphenol A and Phthalate Exposures and Child Neurodevelopment

Abstract: Purpose of Review: Bisphenol A and phthalate have been found in the environment, as well as in humans. In this narrative review pre- and postnatal bisphenol A and phthalate exposures, their relationship to neurodevelopment, and the behavioral outcomes of children are elucidated, focusing in particular on the recent case-control, cross-sectional, and longitudinal studies. This review also introduces some of the possible mechanisms behind the observed associations between exposures and outcomes. Recent Findings:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 114 publications
1
48
0
Order By: Relevance
“…Increases in the caprolactam pathway are interesting because they have been associated with longevity in humans, and high levels of caprolactam metabolising bacteria may provide a protection against toxins in the environment. Environmental toxins such as plastics and synthetic organic compounds have an impact on mental health ( Daniel et al, 2020 ; Minatoya and Kishi, 2021 ; Schirmer et al, 2021 ) and our results raise the possibility that LI-rTMS may facilitate the growth of micro-organisms that can breakdown these compounds, potentially provide a protective effect. It will be important in future studies to determine whether the bacterial changes identified in this study actively contribute to the changes in behaviour, or are merely a consequence of the different interventions.…”
Section: Discussionmentioning
confidence: 70%
“…Increases in the caprolactam pathway are interesting because they have been associated with longevity in humans, and high levels of caprolactam metabolising bacteria may provide a protection against toxins in the environment. Environmental toxins such as plastics and synthetic organic compounds have an impact on mental health ( Daniel et al, 2020 ; Minatoya and Kishi, 2021 ; Schirmer et al, 2021 ) and our results raise the possibility that LI-rTMS may facilitate the growth of micro-organisms that can breakdown these compounds, potentially provide a protective effect. It will be important in future studies to determine whether the bacterial changes identified in this study actively contribute to the changes in behaviour, or are merely a consequence of the different interventions.…”
Section: Discussionmentioning
confidence: 70%
“…Radke et al have underlined that for each phthalate/outcome combination, there was slight or indeterminate evidence of an association, with the exception of motor effects for BBP, for which moderate evidence has been noted [ 30 ]. Minatoya and Kishi have concluded that prenatal exposure to phthalates may contribute to neurobehavioural outcomes in children, but the evidence is still limited [ 29 ]. Another review, the one by Palanza et al (2021) underlined that animal and human studies demonstrate the evidence that EDCs exposure during critical periods of development affects sex differences in emotional and cognitive behaviours [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some authors highlighted the importance of altered sex-specific differences in infant and child neurodevelopment [ 19 , 24 , 28 ]. There are several reviews summarizing the existing evidence on this topic [ 19 , 24 , 25 , 28 , 29 , 30 ]. Ejaredar et al, (2015), in a systematic review of the literature including studies published until year 2014, reported that boys were more prone to adverse behavioural and cognitive effects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among pyrethroid molecules, cypermethrin (CYPE) was also selected due to its wide use in agriculture, veterinary, and medical applications as insecticide and biocide. Finally, for their wide use as additives (plasticizers) in the plastics industry, food packaging and food contact materials, the phthalates DEHP and DBP and the bisphenol BPA have been selected for their well-known characteristics of EDs [97][98][99].…”
Section: Pesticides/biocides and Plasticizersmentioning
confidence: 99%